Superstring theory - Green, Michael B.; Schwarz, John H.; Witten Edward (UK: Cambridge University Press, 1987)
In recent years, superstring theory has emerged as a promising approach to reconciling general relativity with quantum mechanics and unifying the fundamental interactions. Problems that have seemed insuperable in previous approaches take on a totally new character in the context of superstring theory, and some of them have been overcome. Interest in the subject has greatly increased following a succession of exciting recent developments. This two-volume book attempts to meet the need for a systematic exposition of superstring theory and its applications accessible to as wide an audience as possible.
Bibliographical references 435-464p.; Index 465-470p.
Keywords: Basonic string; String theory; Supersymmetry; Tree amtiudes; Physics